Role of 14-3-3 protein family in the pathobiology of EBV in immortalized B cells and Alzheimer’s disease - Awasthi, Prankur; Kumar, Dhruv; Hasan, Saba (Frontiers in Molecular Biosciences, 2024)
Several studies have revealed that infection of EBV raised the likelihood of developing Alzheimer's disease, via infecting B-lymphocytes. The purpose of the current investigation is to assess the possible association between EBV infection and AD.The microarray datasets GSE49628, GSE126379, GSE122063, GSE132903 were utilized to extract DEGs by using GEO2R tool of GEO platform. The STRING tool was used to determine the interaction between the DEGs, and Cytoscape was used to visualize the results.The DEGs that were found underwent function analysis, including pathway and GO, using the DAVID 2021 and ClueGo/CluePedia. By using MNC, MCC, Degree, Radiality of cytoHubba, we identified seven common key genes. Gene co-expression analysis was performed through GeneMANIA web tool. Further, key gene's expression analysis was performed through GTEx software that have been identified in various human brain regions. miRNA-gene interaction was performed through miRNet v 2.0 tool. DsigDB on Enrichr platform was utilised to extract therapeutic drugs connected to key genes.In GEO2R analysis of datasets with |log2FC|≥ 0.5 and p-value <0.05, 8386, 10434, 7408, 759 genes were identified respectively. 141 common DEGs were identified through combining the extracted genes of different datasets. 141 nodes, 207 edges were found during PPI analysis. The DEGs GO analysis with substantial alterations disclosed that they are associated to MF and BP, such as positive regulation of neuron death, autophagy regulation of mitochondrion, response of cell to insulin stimulus, calcium signaling regulation, Organelle transport along microtubule, protein kinase activity, phosphoserine binding. KEGG analysis discovered the correlation between the DEGs in pathways of neurodegeneration -multiple disease, cell cycle, cGMP-PKG signaling pathway. Finally, YWHAH, YWHAG, YWHAB, YWHAZ, MAP2K1, PPP2CA, TUBB genes were identified that are strongly linked to EBV and AD. Three miRNAs i.e., hsa-mir-15a-5p, hsa-let-7a-5p, and hsa-mir-7-5p were identified to regulate most of hub genes which are associated with EBV and AD. Further top ten significant therapeutic drugs were predicted.We have discovered new biomarkers and therapeutic targets for AD, as well as the possible biological mechanisms by whereby infection with EBV may be involved to AD susceptibility for the first time.